Continuous methane concentration measurements at the Greenland ice sheet–atmosphere interface using a low-cost, low-power metal oxide sensor system - C. J. Jørgensen; J. Mønster; K. Fuglsang; J. R. Christiansen (Atmospheric Measurement Techniques, 2020)
In this paper, the performance of a low-cost and low-power methane ( CH 4 ) sensing system prototype based on a metal oxide sensor (MOS) sensitive to CH 4 is tested in a natural CH 4 -emitting environment at the Greenland ice sheet (GrIS). We investigate if the MOS could be used as a supplementary measurement technique for monitoring CH 4 emissions from the GrIS with the scope of setting up a CH 4 monitoring network along the GrIS. The performance of the MOS is evaluated on the basis of simultaneous measurements using a cavity ring-down spectroscopy (CRDS) reference instrument for CH 4 over a field calibration period of approximately 100 h. Results from the field calibration period show that CH 4 concentrations measured with the MOS are in very good agreement with the reference CRDS. The absolute concentration difference between the MOS and the CRDS reference values within the measured concentration range of approximately 2–100 ppm CH 4 was generally lower than 5 ppm CH 4 , while the relative concentration deviations between the MOS and the CRDS were generally below 10 %. The calculated root-mean-square error (RMSE) for the entire field calibration period was 1.69 ppm ( n =37 140 ). The results confirm that low-cost and low-power MOSs can be effectively used for atmospheric CH 4 measurements under stable water vapor conditions. The primary scientific importance of the study is that it provides a clear example of how the application of low-cost technology can enhance our future understanding on the climatic feedbacks from the cryosphere to the atmosphere.